1997
DOI: 10.1046/j.1471-4159.1997.69062608.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Protein Kinase C Activation on the Release of [3H]Acetylcholine in the Presence of Vesamicol

Abstract: The present work tested whether pharmacological activation of protein kinase C (PKC) influences the release of [3H]‐acetylcholine ([3H]ACh) synthesized in the presence of vesamicol, an inhibitor of the vesicular acetylcholine transporter (VAChT). Newly synthesized [3H]ACh was released from hippocampal slices by field stimulation (15 Hz) in the absence of vesamicol, but as expected [3H]ACh synthesized during exposure to vesamicol was not released significantly by stimulation. Treatment of slices with the PKC ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 13 publications
1
23
0
Order By: Relevance
“…3 H]choline and monitored the release of labeled neurotransmitter as previously described (2,26,27,32). VAChT del/del mice are capable of producing ACh (see Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 H]choline and monitored the release of labeled neurotransmitter as previously described (2,26,27,32). VAChT del/del mice are capable of producing ACh (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of previously reported studies suggested that distinct pathways of ACh secretion might exist at cholinergic synapses (56,60,61,64). Moreover, vesamicol-independent ACh release, presumably from synaptic vesicles, can be detected in response to pharmacological treatments (2,7,10,11,46). Hence, if VAChT-independent mechanisms of ACh release have functional significance, they might partially compensate for the lack of the transporter in at least some of its physiological roles.…”
Section: Discussionmentioning
confidence: 99%
“…Slices were obtained from the striatum and hippocampus of control and test mice, labelled with [ 3 H]methyl-choline, and the release of labelled ACh was determined essentially as described [73] except that 33 mM KCl was used as a depolarizing stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, beads were precipitated and washed 5 times with homogenization buffer and after the last wash beads were resuspended in SDS‐sample buffer. Proteins were resolved by sodium dodecyl sulfate‐polyacrylamide gel electrophoresis (SDS‐PAGE) and transferred to nitrocellulose membrane as described (Barbosa et al . 1997).…”
Section: Western Blotting and Precipitation Experimentsmentioning
confidence: 99%